Odpowiedź :
Szczegółowe wyjaśnienie:
6 + (-4) + (-10)= 6-4-10 = 2-10 = -8
-4 - (-9) - 3 = -4+9-3=5-3=2
-16 + 7 - 28 = -9-28=-37
4,3 - 7,4 + 1,1 = -3,1+1,1=-2
-6,2 + 1,6 - (2,3) =-4,6-2,3=-6,9
7,8 - 5,3 - 12,1 =2,5-12,1=-9,6
-1 1/3 - 2/9 + 1/6 = -14/9 +1/6 = -25/18
1 1/8 - 2 1/4 - (-1/2) =-9/8 +1/2=-5/8
-2,1 + 1/5 - 3 = -19/10-3= -49/10
Odpowiedź:
-8
2
-37
-2
-6,9
-9,6
-33/9 -2/9 + 1,5/9 =-(35,9) +1,5/9 = -33,5/9
11/8 - 42/8 +4/8 = -31/8 + 4/8 = -(27/8)
-2,1 +0,2 -3 = - 4,9
Pozdrawiam i licze na naj ;)
Szczegółowe wyjaśnienie: